ANALISIS TANDA DALAM FILM INFERNO KARYA DAN BROWN (Suatu Kajian Semiotika) - Katiandagho, Ekaristi Glory; Rambing, Rosalina; Lotulung, Donald R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â ABSTRACTÂ  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â Ekaristi Glory Katiandagho1Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Dra. Rosalina R. Rambing, DEA2Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Donald R. Lotulung, S.S, M.Hum3Â  Â  Â  This research entitles â€œAnalisis Tanda dalam Film Inferno Karya Dan Brown: Suatu Analisis Semiotikâ€. The aims of this research are to identify, classify, and analyze the kinds and meaning of signs in Inferno film. In this research, the writer uses Peirceâ€™s theory in the process of identifying, classifying, and analyzing each scene containing the signs used the representamen aspect. The method of this research is descriptive. In doing this research, the writer read some books, semiotics journal, articles, and also downloaded resources from the internet. The data of signs were collected from every scene which contains sign in the film and analyzed according to Pierceâ€™s theory. The result of this research shows that there are three kinds of signs in film, namely icons, index, and symbols. There are 9 icons, 4 indexes, and 17 symbols. They were found from 25 scenes in the Inferno film and each sign has different meanings.Keywords: Sign, Inferno Film, Semiotic Analysis